2014
DOI: 10.1515/peps-2013-0053
|View full text |Cite
|
Sign up to set email alerts
|

Illegal Gold Mining and Violence in Colombia

Abstract: The increase in the international price of commodities after the international financial crisis in 2008 produced a gold rush in the Colombian economy, making legal and illegal mining a very profitable and attractive business. The increase in the illegal exploitation of metals like gold has exacerbated violence in municipalities with an abundance of such minerals. Gold is believed to be a new engine in the Colombian conflict. This paper documents the phenomenon and quantifies the causal impact that the gold boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 20 publications
1
33
0
2
Order By: Relevance
“…The hypothesis that armed groups try to protect their sources of finance violently is consistent with the results of Idrobo et al (2013), and Abadie et al (2013). 12 There are four main variables for the MPI that are not included in the 1993 Census: i) access to childcare services, ii) affiliation to a pension fund (proxy of formality), iii) health insurance coverage, and iv) access to health services in case of need.…”
Section: Datasupporting
confidence: 82%
“…The hypothesis that armed groups try to protect their sources of finance violently is consistent with the results of Idrobo et al (2013), and Abadie et al (2013). 12 There are four main variables for the MPI that are not included in the 1993 Census: i) access to childcare services, ii) affiliation to a pension fund (proxy of formality), iii) health insurance coverage, and iv) access to health services in case of need.…”
Section: Datasupporting
confidence: 82%
“…However, few academic studies have examined in detail the side effects of the recent mining boom (legal and illegal) on the levels of violence. A recent social science paper that quantified the causal impact of the gold boom on indicators of violence such as homicides, forced displacements and massacres, found that the recent gold rush has become a new driving force in territorial conflicts and has exacerbated violence in gang-controlled (but not corporation-controlled) gold mining areas [13]. In light of this situation and the lack of an updated mining census, the Colombian Comptroller General (Contraloria de la República), which is a monitoring agency, has called for a moratorium or "standby" to granting any new mining concessions until the sector can be properly managed and administered to benefit Colombia [6].…”
Section: Impact Of Industrial Miningmentioning
confidence: 99%
“…Demonstrating a statistically significant increase in homicides and massacres in municipalities with gold production, Idrobo et al (2014) believe that gold is 'the new engine in the Colombian conflict ' (p. 4).…”
Section: Growing Resistance Against the Mining Industrymentioning
confidence: 99%